Web-Crippling Behaviour of Cold-Formed Screw Fastened Rectangular Hollow Flange Z-Section Beams Under Two-Flange Load Cases - Siva, Koppala; Visuvasam, Joseph Antony (Salehan Institute of Higher Education, 2025)
This study investigates to update the web-crippling coefficients of cold-formed screw-fastened hollow flange Z-section (SFHZ) beams under End-Two-Flange (ETF) and Interior-Two-Flange (ITF) loading conditions. As coefficients are available in AISI standards to estimate the web crippling capacity of Z-sections, experimental program is carried out on 48 number of SFHZ specimens. An extensive parametric study considering the effects of web slenderness, material strength, and support length is conducted for 240 finite element models. Both experimental results and Finite Element Analysis (FEA) were used to predict web-crippling capacities and verified with current AISI predictions. The findings reveal that existing specifications are un-conservative for both ETF and ITF load cases. The parameters such as web height-to-thickness, inside bend radius-to-thickness, and bearing length-to-thickness ratios are the key factors influencing the prediction of web crippling capacity of SFHZ sections. As a result, the study proposes updated web-crippling coefficients that offer improved accuracy in predicting SFHZ section performance under two-flange loading conditions.